Description of the method of fuzzy situational control based on a composite hybrid model of a complex technical system - D. Yu. Avramenko (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The aim of the study is to generalize the accumulated experience of fuzzy situational control based on a compositional hybrid model of a complex technical system in the form of an algorithm and, on this basis, to form recommendations on the methodology for the formation and identification of situations, determining parameters and solutions for managing a complex technical system under conditions incomplete data to improve the accuracy of control decisions. Method. The use of a compositional hybrid model solves the problem of describing and modeling the system in conditions of incomplete data and the impossibility of obtaining information about the entire range of the system's operation. Fuzzy situational control makes it possible to develop control decisions in accordance with the chosen control strategy and take into account the specifics of the system thanks to the compositional model. Result. An algorithm for fuzzy situational control of complex technical systems based on compositional hybrid models is proposed. The stages, features, advantages and disadvantages of fuzzy situational control for this type of systems are considered. The procedure for determining and unambiguously identifying emerging fuzzy situations for the system is given, and a method for analyzing and developing typical control strategies is also considered. The compositional hybrid model of a complex technical system considered in the article describes the operation of the experimental compressor unit ETsK-55. Conclusion. The main advantages of the developed fuzzy situational method for managing complex technical systems include: integration of the control system with existing elements of the system; better use of available resources; adaptability and reliability of a control method based on fuzzy situational networks and a composite hybrid model of the system. Management strategies have been defined to meet the customer's requirements for product quality, as well as the safety of personnel and equipment, trouble-free production and saving resources.